The ghosts of Gwendolyn Montgomery : a novel - Haynes, Clarence A. (Legacy Lit, 2025)
"In a fast-paced, sexy, ghostly adventure, a publicist at the top of her game must confront her secret mystical past. To be a client of Gwendolyn Montgomery's-New York's most powerful publicist at Sublime Media-is to be infused with a certain oomph, a mysterious glamour. She seems to have created the ideal life with her handsome new boyfriend, the perfect match. But Gwendolyn has a secret: She's a mystical practitioner who can tap into the interdimensional, metaphysical realm of the dead known as El Intermedio. Gwendolyn has hidden her powers, buried her old life, and started anew. After a grisly, bizarre incident at the Brooklyn Museum, Gwendolyn begins to realize that something nefarious is happening tied directly to her past, right as Fonsi Harewood comes back into her world. Fonsi is a queer Latinx psychic from the South Bronx who's caught up in a love triangle with a ghost and his mortal ex. He's able to communicate with the dead, having established a robust business interpreting messages from departed loved ones. And he comes with a dire warning for Gwendolyn that the barrier between humans and spirits is weakening. Gwendolyn would prefer not to have anything to do with ghostly drama. Yet in order to get to the bottom of the spookiness derailing her life, she must face the demons she'd long left behind. Or the spirit world will be unleashed, threatening her very existence and all of New York. The Ghosts of Gwendolyn Montgomery is a sensuous, funny, mystical adventure that will leave you spellbound as you keep the pages turning"--